2020
DOI: 10.3390/ani10122406
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Parameters of Bovine Milk Fatty Acid Profile, Yield, Composition, Total and Differential Somatic Cell Count

Abstract: The growing interest of consumers for milk and dairy products of high nutritional value has pushed researchers to evaluate the feasibility of including fatty acids (FA) in selection programs to modify milk fat profile and improve its nutritional quality. Therefore, the aim of this study was to estimate genetic parameters of FA profile predicted by mid-infrared spectroscopy, milk yield, composition, and total and differential somatic cell count. Edited data included 35,331 test-day records of 25,407 Italian Hol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 38 publications
1
13
2
Order By: Relevance
“…Except for genetic correlations between group FAs with somatic cell scores, other correlations were significant. A similarly focused study [ 4 ] found the same tendencies in genetic correlations. Negative correlations with milk and protein yield and positive correlations with the percentage of fat, protein and casein.…”
Section: Introductionmentioning
confidence: 52%
See 2 more Smart Citations
“…Except for genetic correlations between group FAs with somatic cell scores, other correlations were significant. A similarly focused study [ 4 ] found the same tendencies in genetic correlations. Negative correlations with milk and protein yield and positive correlations with the percentage of fat, protein and casein.…”
Section: Introductionmentioning
confidence: 52%
“…Authors calculated with results of 885,249 repeated test-day milk records. Heritability values may also reflect the origins of FA (performed or synthesized de novo) and their grouping according to saturation or chain length [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some critical features directly impact the milk yield and production capacity [ 10 ]. There is a strong correlation in various production metrics, such as fat content and milk yield, protein content, milk urea nitrogen, and somatic cell count [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a useful proxy to assess mastitis is milk somatic cell count (SCC) and its log transformation somatic cell score (SCS): an index that evaluates the inflammatory status of the mammary gland, which has been widely used to monitor milk quality and udder health [ 16 ], and to select cows with a reduced susceptibility to mastitis [ 17 ]. Furthermore, heritability of SCS was assessed to be low-to-moderate (e.g., 0.05 to 0.10) [ 17 , 18 ], thus suggesting the possibility of performing genetic selection [ 19 ]. More specifically, genomic selection could be of use when dealing with low-to-moderate heritability traits [ 20 ].…”
Section: Introductionmentioning
confidence: 99%